Pengembangan Literasi Komputer Guru Di SMA Putra Bangsa Depok Melalui Pelatihan Pemanfaatan Microsoft Excel - Vickry Ramdhan; Rahman Abdillah; Fajar Erlangga; Dyah Rhetno Wardhani; Adhityo Kuncoro (CV. Multi Kreasi Media, 2024)
Good and orderly management of student scores in each lesson is the hope of every teacher to make various decisions regarding their students easier. This goal may be realized if teachers have good computer literacy, especially in terms of using Microsoft Excel. However, many of them have still not maximized the use of this program. Based on estimation, it was concluded the teachers at SMA Putra Bangsa Depok had not maximized the use of Microsoft Excel for managing their students' scores. So, the community service team, through this community service, tried to provide education and disseminate knowledge regarding the optimal use of Microsoft Excel program that it could be used as a guide in maximizing of the objectives of implementing each activity which are expected to be achieved. The result provides an increase in teachers’ computer literacy, especially in Microsoft Excel.